W sprawie granicy między prowincjami rzymskimi Syrią Coele i Syrią Phoenice = Concerning the border between the Roman provinces of Syria Coele and Syria Phoenice - Filipczak, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The border between the provinces of Syria Coele and Syria Phoenice, created by Emperor Septimius Severus, is not precisely known. Both provinces had exactly the same name (Syria Coele) or almost the same name (Syria Phoenice), as the geographical and historical lands described for a long time in Greek and Roman literature. However, the provinces did not cover the same area as the geographical regions.
Keywords: Syria; Fenicja; Syria Coele; Syria Phoenice; prowincja; Phoenice; province